0.017779534 because you just divide it
answer the original number is 6
(5x + 2 - 10) *2 = 44
10x + -16 = 44
10x = 60
x=6
Answer:
-4 ± 2√6
Step-by-step explanation:
Rewritten in standard quadratic form, x^2+8x-2=18 becomes x^2 + 8x - 20 = 0.
Here the quadratic coefficients are a = 1, b = 8 and c = -20 and so the discriminant is b^2 - 4ac, or 8^2 - 4(1)(-20), or 96.
Because the discriminant is positive, we know that this quadratic has two different real roots. These roots are:
-b ± √(b² - 4ac)
x = -------------------------
2a
which in this case comes out to:
-8 ± √96 -8 ± 4√6
x = ------------------ = ------------------- = -4 ± 2√6
2 2
Answer:
3.6 3/6 3.6 percent 3:6
Step-by-step explanation:
10:9
15:14
20:19
Answer:
x^2 - 12x = -27
Step-by-step explanation:
Here, we want to isolate the constant for the polynomial
To do this, we start by setting the expression to zero
Afterwards, we can bring the constant term over the equal to sign, giving a change in sign value
Mathematically, we have this as;
x^2 - 12x + 27 = 0
x^2 - 12x = -27